Coaching for Empowering Digital Marketing for MSMEs in Malang City: A Case Study of the Community-Based Approach: Pendampingan Pemberdayaan Digital Marketing UMKM Kota Malang: Studi Kasus Comunity Based Approach - Fifi Nur Faizah; Eko Nurhadi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
UMKMs in Malang City face various challenges in optimizing the use of Instagram as a social media platform, including low technological proficiency, inconsistency in social media management, limited creativity in content creation, and inadequate understanding of product branding. To address these challenges, a community service program was implemented with the aim of enhancing the skills and empowering MSME actors through the application of a Community-Based Approach. The program involved four MSMEs under the guidance of Qurota Academy in Malang City. The mentoring activities took place from October 1 to November 12, 2024, encompassing training sessions, intensive mentoring, and community-based evaluations that placed MSME actors at the center of the entire process. The results of the program showed that 50% of participants successfully applied the knowledge gained during the activities, while the remaining 50% required further assistance for optimal implementation. This program is expected to serve as a sustainable empowerment model for UMKMs in Malang City